AMBIGUITAS MEDIA DALAM MASYARAKAT: PERTARUNGAN ANTARA AS IT IS & AS OUGHT TO BE - Inggrit W., Inri (Institute of Research and Community Outreach - Petra Christian University, 2009)
Information and Communication Technologies is the effect of globalization, thus makes media become an actor for trasformation and the rapidth of communication stream. In Indonesia, democratization that had been began by reformation in 1998 then as a proof of the strengthness of information technology that was succed bringing the great changes for Indonesian politic. The fall of The New Order in 1998, could not be separated from the role of internet which at that time offered the public sphere and the freedom to receive and exchange information without government intervention. The history of the journey of media, including Indonesia, media often face a dilema. Media was experiencing an ambiguty, facing the conflict of interest between as ought to be and as it is. Will media keep their ideal function as the icon of democratization that provide information for reaching transparation and partisipation of society in policy making process ? It is related to the freedom of information for society. Media are also expected to be conistent for always acomodating varies opinions or inputs of society. In other side, media are controled by capitalism which then makes media to serve the capitalis’s interest as well as make a priority for the economy aspect in producing the information.